A historical trajectory of Financial Education: from OEEC to the new ENEF - Silva, Priscila de Oliveira e; Mazzi, Lucas Carato (Educação Matemática Debate, 2024)
This paper discusses the relevant historical aspects of Financial Education. The aim is to contribute to a broad understanding of how the subject has been built up, changed and become an everyday topic. We start from the creation of the Organisation for European Economic Co-operation (OEEC), through the Organisation for Economic Cooperation and Development (OECD), which developed Financial Education, until we arrive in Brazil, with the Estratégia Nacional de Educação Financeira (ENEF — National Strategy for Financial Education), in 2010, updated in 2020. The historical trajectory of the OECD and ENEF proposals shows a market approach to Financial Education. Over the years, in the context of education and Mathematics Education, discussions have matured, resulting in a Financial Education that questions the neoliberal system and seeks social transformation.